ANALYSIS OF RESULTS OF DNA ISOLATION FROM BIOLOGICAL SAMPLES [Text] - Ichshanova, A.S.; Radojicic, B.; Ищанова, А.С. (Наука и образование №4, 2018)
To date, researchers have a fairly large set of methods for extracting and purifying DNA, and these methods continue to be improved and modified with reference to new research objects. In connection with the variety of living objects, there are no universal methods of DNA isolation. The use of this or that method of DNA isolation is dictated, firstly, by the specificity of the material being studied, and secondly, by what purpose is pursued: the production of total, nuclear, chloroplast DNA or other of its preparations. The DNA isolation method should be relatively simple, well reproducible and allow for the rapid production of sufficient quantities of satisfactorily purified DNA preparations. The yield of DNA depends on the nature of the starting material and is due to the content of DNA in this tissue, as well as the presence and nature of impurities that interfere with DNA purification.К настоящему времени в арсенале исследователей имеется довольно большой набор методов экстракции и очистки ДНК, причем эти методы продолжают совершенствоваться и модифицироваться применительно к новым объектам исследования. В связи с разнообразием живых объектов универсальных методов выделения ДНК не существует. Использование того или иного метода выделения ДНК диктуется, во-первых, спецификой изучаемого материала, а во-вторых, тем, какая преследуется цель: получение суммарной, ядерной, хлоропластной ДНК или других ее препаратов. Метод выделения ДНК должен быть относительно простым, хорошо воспроизводимым и давать возможность быстрого получения достаточных количеств удовлетворительно очищенных препаратов ДНК. Выход ДНК зависит от природы исходного материала и обусловлен содержанием ДНК в данной ткани, а также наличием и характером примесей, препятствующих очистке ДНК. В статье на основании литературных источников и собственных исследований приведены результаты исследований по выбору оптимального метода выделения ДНК Pasteurella multocida из биологического материала.
Keywords: рк; научный журнал; отечественное издание; периодическое издание; журнал кксон; ветеринария; днк; геномная днк; очистка днк; dna (deoxyribonucleic acid); electrophoresis; commercial reagent kit